2013
DOI: 10.5210/fm.v18i4.4296
|View full text |Cite
|
Sign up to set email alerts
|

Scientists’ use of social media: The case of researchers at the University of the Philippines Los Baños

Abstract: Using proportional random sampling, 86 researchers working at the University of the Philippines Los Baños (UPLB) were chosen as respondents of a survey study that aimed to determine scientists’ perceptions and use of social media for research. The study also investigated the influence of several factors — age, awareness, Internet connectivity, research style, and technology adoption behavior — on the scientists’ use of social media in research and research–related activities. Results showed that age, connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…More precisely, research conducted by CIBER (cited in Cruz and Jamias 2013) showed that researchers use social media at all stages in their research workflow, but particularly for: 1. identification of research opportunities 2. identification of potential collaboration with peers outside their immediate network 3. securing research funding support 4. review of literature 5. collection of research data 6. analysis of research data 7. dissemination of findings 8. management of the research process…”
Section: Web 20 Social Media and Networking Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, research conducted by CIBER (cited in Cruz and Jamias 2013) showed that researchers use social media at all stages in their research workflow, but particularly for: 1. identification of research opportunities 2. identification of potential collaboration with peers outside their immediate network 3. securing research funding support 4. review of literature 5. collection of research data 6. analysis of research data 7. dissemination of findings 8. management of the research process…”
Section: Web 20 Social Media and Networking Sitesmentioning
confidence: 99%
“…For instance, Mendeley and Twitter are becoming increasingly well integrated in researchers' workflows and processes. Mendeley seems to be particularly useful for reviewing the literature, along with wikis, Google Docs or Academia (Cruz and Jamias 2013). Other studies -for instance, Coppock and Davis (2013) -argue however that social media do not bring anything more to the discovery of research information as this function is already well performed by existing commercial platforms and associated tools.…”
Section: Rate Of Adoption Of Web 20 Technologiesmentioning
confidence: 99%
“…Other social media had a considerably lower uptake in this group. Cruz and Jamias (2013) surveyed researchers at the University of the Philippines Los Baños on their use of social media. They found that awareness of social media did not indicate use.…”
Section: Descriptive Content Analysismentioning
confidence: 99%
“…Their use of social media for academic activities is a process of satisfying specific needs and motivations. Awareness of social media tools roughly translates into actual use of social media (Cruz and Jamias, 2013). At the same time, researchers can deduce their attitudes through their external behavior and the prevailing environment.…”
Section: Research Objectivesmentioning
confidence: 99%